2004
DOI: 10.1089/jir.2004.24.543
|View full text |Cite
|
Sign up to set email alerts
|

TLR2 and TLR4 Stimulation Differentially Induce Cytokine Secretion in Human Neonatal, Adult, and Murine Mononuclear Cells

Abstract: Toll-like receptor 2 (TLR2) and TLR4 signaling may induce differential secretion of T helper 1 (Th1) and Th2 cytokines, potentially influencing the development of autoimmune or atopic diseases. To date, the influence of the type of stimulus, timing, and dose of TLR2 and TLR4 ligands on cytokine secretion has not been well established. We tested whether the innate stimuli peptidoglycan (Ppg, TLR2 agonist) and lipid A (LpA, TLR4 agonist) differentially affect the secretion of interleukin-13 (IL-13) (Th2) and int… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

2
34
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 38 publications
(36 citation statements)
references
References 61 publications
2
34
0
Order By: Relevance
“…A recent study compared the effects of Lipid A in terms of maturity of the immune system, species, dose, and timing by examination of human cord and adult PBMCs and murine cells in vitro and in vivo. 13 Lipid A induced primarily a time-and dose-independent production of IFN-g.…”
Section: Discussionmentioning
confidence: 91%
See 1 more Smart Citation
“…A recent study compared the effects of Lipid A in terms of maturity of the immune system, species, dose, and timing by examination of human cord and adult PBMCs and murine cells in vitro and in vivo. 13 Lipid A induced primarily a time-and dose-independent production of IFN-g.…”
Section: Discussionmentioning
confidence: 91%
“…Adaptive immune processes, including activation of helper T lymphocytes and subsequent B-lymphocyte activation with IgE isotype switching, underlie the process of allergic sensitization in individuals genetically predisposed to development of allergic responses. 6 Although still controversial, 7,8 there is mounting evidence from animal models [9][10][11][12][13] and the epidemiologic literature 14,15 suggesting that exposure to endotoxin, a potent activator of innate immunity, might influence subsequent adaptive immune responses to allergen. Furthermore, these studies suggest that the timing and dose of endotoxin exposure influence the nature of the immune response, leading to the hypothesis that early life might be a crucial time window during which endotoxin might reduce the risk of allergy through its influence on innate immunity and downstream T-cell and B-cell regulation of cytokine and IgE expression.…”
mentioning
confidence: 99%
“…11,14,15 Significant changes through endotoxin were excluded. After incubation with 3 H-Thymidine for additional 8 hours, cells were analyzed for lymphocyte proliferation, assessed by counts per minute (cpm), and quantified by stimulation index (SI), representing the ratio of mean cpm of stimulated/unstimulated replicates.…”
Section: Lymphocyte Proliferation Cytokine Secretion Of Cbmcsmentioning
confidence: 99%
“…It has repeatedly been shown that children growing up in environments rich in microbial stimuli, particularly in the first year of life, are at lower risk of allergies. 2,9 Toll-like receptor (TLR)-2 and TLR4, 2 key receptors (for peptidoglycan and lipid A) of innate immune activation, have been shown to be differentially regulated in mice and children early in life 10,11 and were increased in children exposed to high amounts of innate microbial stimuli. 12,13 Here, we aimed to examine cord blood for differences in T-cell subpopulations under different conditions of TLR2, TLR4, and mitogen/adaptive stimulation.…”
mentioning
confidence: 99%
“…Murine asthma models, as well as epidemiologic studies, suggest that exposure to LPS or its bioactive components is associated with a decrease in allergic asthma [52,53]. The relationship of innate immunity to allergic adaptive responses is under investigation [54,55]. The activation or inhibition of costimulatory molecules related to outcomes of human allergic disease is an area of major interest, and is being pursued in murine-allergic models, as described later.…”
Section: Costimulation and Innate Immunitymentioning
confidence: 99%